Catheter Ablation of Stable Ventricular Tachycardia Before Defibrillator Implantation in Patients with Coronary Heart Disease (VTACH): An On‐Treatment Analysis. (25th January 2013) - DELACRÉTAZ, ETIENNE; BRENNER, ROMAN; SCHAUMANN, ANSELM; ECKARDT, LARS; WILLEMS, STEPHAN; PITSCHNER, HEINZ‐FRIEDRICH; KAUTZNER, JOSEF; SCHUMACHER, BURGHARD; HANSEN, PETER S.; KUCK, KARL‐HEINZ; ,
Catheter Ablation of Stable Ventricular Tachycardia : Background: In the Ventricular Tachycardia Ablation in Coronary Heart Disease (VTACH) study, an intention‐to‐treat approach was used and may have diminished the observed degree of treatment effect. We present a subanalysis of the VTACH study by treatment actually received. Methods and Results: The VTACH study was a prospective, open, randomized controlled trial, undertaken in 16 European centers, comparing defibrillator implantation with and without ventricular tachycardia (VT) ablation in patients with stable VT, previous myocardial infarction, and reduced left‐ventricular ejection fraction. Of the 52 patients in the ablation group, 7 (13%) did not receive VT ablation and 19% of patients assigned to implantable cardioverter defibrillator (ICD) only treatment group crossed over and had an ablation. The primary endpoint (first recurrence of any documented VT or ventricular fibrillation [VF]) was reached after a median of 19.5 months in the ablation group and 5.9 months in the ICD only group (P = 0.01). Overall, 685 VT/VF events occurred per year of follow‐up in 22 patients of the ablation group and 4, 986 events in 43 patients of the control group (P = 0.024). In the ICD only group, median numbers of VT/VF episodes were 25 (IQR 5.8–45.3) and 1.5 (IQR 0–24.8) per patient and year before and after crossover (n = 12), respectively. Conclusion: On‐treatment analysis of the VTACH study emphasizes the effectiveness of VT ablation in patients receiving ICD treatment because of monomorphic VT post myocardial infarction. VT ablation clearly prolonged time to recurrence of VT/VF episodes and markedly decreased VT/VF burden.